Methylcellulose – a versatile printing material that enables biofabrication of tissue equivalents with high shape fidelity. (1st April 2020) - Ahlfeld, T.; Guduric, V.; Duin, S.; Akkineni, A. R.; Schütz, K.; Kilian, D.; Emmermacher, J.; Cubo-Mateo, N.; Dani, S.; Witzleben, M. v.; Spangenberg, J.; Abdelgaber, R.; et al.
Abstract : This minireview highlights the use of the polysaccharide methylcellulose for biofabrication applications. Its properties are useful for printing of dissolvable support structures as well as the development of novel bioinks. Abstract : With the aid of biofabrication, cells can be spatially arranged in three dimensions, which offers the opportunity to guide tissue maturation in a better way compared to traditional tissue engineering approaches. A prominent technique allowing biofabrication of tissue equivalents is extrusion-based 3D (bio)printing, also called 3D (bio)plotting or robocasting, which comprises cells embedded in the biomaterial (bioink) during the fabrication process. First bioprinting studies introduced bioinks allowing either good cell viability or good shape fidelity. Concepts enabling printing of cell-laden constructs with high shape fidelity were developed only rarely. Recent studies showed the great potential of the polysaccharide methylcellulose (mc) as supportive biomaterial that can be utilized in various ways to enable biofabrication and especially extrusion-based bioprinting of bioinks. This minireview highlights the multiple applications of mc for biofabrication: it was successfully used as sacrificial ink to enable 3D shaping of cell sheets or biomaterial inks as well as as internal stabilizing component of various bioinks. Moreover, a brief overview about first bioprinted functional tissue equivalents is given, which have been fabricated by using mc. Based on these studies, future research should consider mc as an auxiliary material for bioinks and biofabricated constructs with high shape fidelity.